Accelerated Orthodontic Tooth Movement - From Theoretical Knowledge to Clinical Implementation - Boni Guessou, Sabi Sika (Archive of Orofacial Data Science, 2025)
AIM: This review aims to evaluate the efficiency of Accelerated Orthodontic Tooth Movement (AOTM) compared to conventional methods in terms of tooth movement speed and treatment duration, and to assess the existing evidence in current research. METHODS: An electronic search was conducted on PubMed, complemented by a manual search using Readcube software and the websites of selected orthodontic journals. RESULTS: The initial search identified 232 studies, with 40 passing the first review phase, ultimately resulting in the selection of 35 studies. Five AOTM strategies employed in humans include corticotomy / piezotomy, interseptal alveolar surgery, low-intensity laser therapy (LILT), vibration, and biological treatment. CONCLUSION: All AOTM strategies share a common biological basis and are categorised as either stimulation methods or intensification methods. Evidence suggests that surgical strategies, as intensification methods, can accelerate tooth movement during the initial two months of healing, reducing treatment duration by over 50%. Notably, dentoalveolar distraction achieves tooth movement rates of up to 0.8 mm/day, while corticotomy / piezotomy can enhance tooth movement by 41% to 80%. Device-assisted therapeutics approaches are still controversial, whereas LILT may improve tooth alignment by more than 100%. Biological strategies are less explored due to technical challenges.